Pengembangan Ekonomi Lampung Berbasis Wisata Halal - iMRON; Syahrul (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2022)
Interest in sharia tourism must be responded to by developing sharia tourism businesses in Lampung Province, so that it can help move the economy of Lampung Province. Unfortunately, at this time sharia tourism in Lampung Province itself is still being done half-heartedly. It has been proven that it is only limited to conventional tourism development. If it is done well, it will certainly be a huge opportunity, and it has the potential to boost the country's foreign exchange reserves for the Muslim tourist market of Lampung Province. This study uses a qualitative research approach. The increase in tourist visits shows that Lampung Province has a magnet for tourists who want to visit Lampung Province.  The economic potential of halal tourism in Lampung Province can be seen from pilgrimage, culinary and cultural tourism which can continue to be developed into a lucrative economic potential especially with the support of the government and other elements such as academics and practitioners. The opportunity for halal tourism in Lampung Province is very large because the majority of the population of Lampung Province is Muslim and the increasing number of tourists both local and foreign who come to Lampung Province. At the same time, the tourism potential that is owned is also very much in demand. However, several challenges that Lampung Province must also pay attention to are how then the marketing strategy can be carried out properly and accommodate the interests of other tourists (non-Muslims). Therefore, it is very important to develop halal tourism because its influence is not only on the Islamic economic sector but also a source of state income.